2016
DOI: 10.1523/jneurosci.3621-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

Effective Connectivity from Early Visual Cortex to Posterior Occipitotemporal Face Areas Supports Face Selectivity and Predicts Developmental Prosopagnosia

Abstract: Face processing is mediated by interactions between functional areas in the occipital and temporal lobe, and the fusiform face area (FFA) and anterior temporal lobe play key roles in the recognition of facial identity. Individuals with developmental prosopagnosia (DP), a lifelong face recognition impairment, have been shown to have structural and functional neuronal alterations in these areas. The present study investigated how face selectivity is generated in participants with normal face processing, and how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
48
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 49 publications
6
48
0
1
Order By: Relevance
“…The OFA/inferior occipital gyrus appears to be involved at an early stage, while the fusiform gyrus and the superior temporal ROIs (locations of the FFA and STS) are recruited at later time points. This is consistent with a hierarchical model based on feedforward processing of expression (Lohse et al, 2016;Wang et al, 2016). Later time windows are characterized by patterns in the insular, prefrontal and orbitofrontal cortices, previously associated with emotional processing especially at the later stages of integration and evaluation (Chikazoe, Lee, Kriegeskorte, & Anderson, 2014;Phan, Wager, Taylor, & Liberzon, 2002).…”
Section: Spatial Patterns Of Expression-related Informationsupporting
confidence: 88%
“…The OFA/inferior occipital gyrus appears to be involved at an early stage, while the fusiform gyrus and the superior temporal ROIs (locations of the FFA and STS) are recruited at later time points. This is consistent with a hierarchical model based on feedforward processing of expression (Lohse et al, 2016;Wang et al, 2016). Later time windows are characterized by patterns in the insular, prefrontal and orbitofrontal cortices, previously associated with emotional processing especially at the later stages of integration and evaluation (Chikazoe, Lee, Kriegeskorte, & Anderson, 2014;Phan, Wager, Taylor, & Liberzon, 2002).…”
Section: Spatial Patterns Of Expression-related Informationsupporting
confidence: 88%
“…The abnormality of the ATL is evident in the current findings as well, and the analysis, conducted in an assumptionfree fashion revealed that the ATL was the most important hub that distinguished the network topology of the CPs and controls. Together, these findings point to abnormal structure, function and connectivity of this region in CP individuals (but see Gomez et al, 2015;Song et al, 2015;Lohse et al, 2016).…”
Section: The Anterior Temporal Cortexmentioning
confidence: 96%
“…In contrast, more sensitive methods that have been used to map structural changes in CP relative to controls, such as diffusion tensor imaging (DTI) have revealed a reduction in long-range white matter tracts connecting the 'core' face-related posterior patches and the anterior temporal lobe face patch (ATL) in CP Steinbrink et al, 2008;Odegard et al, 2009;Thomas et al, 2009). Other studies have also reported local structural and functional atypical alterations in the vicinity of face-selective regions (Gomez et al, 2015;Song et al, 2015;Lohse et al, 2016). Using standard functional connectivity (FC) analysis, which measures the temporal correlations across different brain areas within an individual, we have previously documented impairments in the connectivity patterns between the 'core' and 'extended' nodes of the face system Behrmann, 2009, 2014;.…”
Section: Introductionmentioning
confidence: 99%
“…The fusiform is sensitive to complex visual stimuli including faces and facial expressions (Li et al, 2019); in the corresponding region of the macaque brain the code determining face cell firing was recently deciphered (Chang and Tsao, 2017). In humans, reduced functional connectivity of the fusiform face area is associated with developmental prosopagnosia (Lohse et al, 2016). The sex difference in functional connectivity we have identified in this region is especially interesting in the context of behavioural data in which female neonates, compared to males, show increased preference for looking at faces (Connellan et al, 2000).…”
Section: Association Networkmentioning
confidence: 99%